Implementation of the Double Diamond Method in Developing the FIRA Financial Reporting Website - Yosia Cristian Surya Wijaya (ESENSI: Jurnal Manajemen Bisnis, 2024)
Digital transformation in regional financial governance demands high data accuracy; however, internal reporting processes in Regional Apparatus Organizations (OPD) often still face significant manual constraints. In the Communication and Informatics Office (Diskominfo) of Karanganyar Regency, the risk of human error in account code selection and bureaucratic inefficiencies are major obstacles before data is entered into the national system, SIPD RI. This study aims to develop the FIRA financial reporting information system as an internal filtration instrument to ensure data integrity. The method used is qualitative descriptive within the Double Diamond Design Model development framework (Discover, Define, Develop, Deliver). Data collection was conducted through in-depth interviews, observation, and documentation, using the Miles and Huberman interactive data analysis model. The results show that the FIRA system successfully integrates previously fragmented business processes into a single centralized platform. Functionality testing using Blackbox Testing on 33 main features demonstrated a 100% accuracy rate and the system's success in independently validating data format uniformity. In conclusion, the implementation of the FIRA system effectively mitigates administrative constraints, eliminates dependency on physical verification, and ensures accurate reporting data before synchronization with SIPD RI